1996
DOI: 10.1007/bf01586182
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in vitro resistance to fluconazole and clinical outcome of oropharyngeal candidiasis in HIV-infected patients

Abstract: Fifty episodes of oropharyngeal candidiasis in HIV-infected patients were analyzed prospectively in order to evaluate the clinical response to fluconazole. The minimum inhibitory concentrations (MICs) of fluconazole for the Candida strains isolated from the pharynx were correlated with the clinical response. Treatment with fluconazole (100 mg/day) was successful in 86% of the cases. A good clinical outcome followed in 97% of the cases when a strain sensitive to fluconazole was isolated. This figure fell to 22%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Using a non-M27 broth-based method, Cartledge et al reported that infections due to isolates with fluconazole MICs of Ͼ8 g/ml were unlikely to respond to 100 mg of fluconazole per day (27). Quereda reported that infections due to isolates with fluconazole MICs of Ն8 g/mL (by M27-A, but in medium supplemented to 20 g of glucose per liter) were less likely to respond to 100 mg of fluconazole per day (173). Using doses of fluconazole that increased from 100 mg/day to as high as 800 mg/day as needed, Revankar et al reported that clinical failure only occurred when the M27-A MIC was Ն64 g/ml (178).…”
Section: Support For the Clinical Relevance Of Nccls M27 Mics In Yeastsmentioning
confidence: 99%
“…Using a non-M27 broth-based method, Cartledge et al reported that infections due to isolates with fluconazole MICs of Ͼ8 g/ml were unlikely to respond to 100 mg of fluconazole per day (27). Quereda reported that infections due to isolates with fluconazole MICs of Ն8 g/mL (by M27-A, but in medium supplemented to 20 g of glucose per liter) were less likely to respond to 100 mg of fluconazole per day (173). Using doses of fluconazole that increased from 100 mg/day to as high as 800 mg/day as needed, Revankar et al reported that clinical failure only occurred when the M27-A MIC was Ն64 g/ml (178).…”
Section: Support For the Clinical Relevance Of Nccls M27 Mics In Yeastsmentioning
confidence: 99%
“…However, when caspofungin was used for the treatment of patients with candidemia, those with C. parapsilosis fungemia (14 of 20) responded as well as those with C. albicans and other species (13 of 20) (8). Therefore, the correlation of in vitro susceptibility and clinical response, at least for C. parapsilosis, does not seem as close for caspofungin as for fluconazole (4,6,12). Additionally, pharmacokinetic considerations such as drug access to sites of infection, distribution in tissue, or clearance may contribute to clinical failure.…”
mentioning
confidence: 99%
“…In recent years azole agents have become the drugs of choice for treating both oropharyngeal candidiasis and VVC (16,18). However, recent studies have indicated the possibility of treatment failures associated with C. albicans resistance to azoles (4,12).…”
mentioning
confidence: 99%